Impact of Alzheimer’s disease and related dementias on colorectal cancer screening utilization, knowledge, and associated health disparities - Lv, Gang; Wang, Xiaoxia; Jiang, Xiangxiang; Li, Minghui; Lu, Kevin (Frontiers in Pharmacology, 2022)
Background: Colorectal cancer screening can detect colorectal cancer at an early stage and reduce mortality. None of the existing clinical practice guidelines provide specific recommendations for colorectal cancer screening in patients with Alzheimer’s disease and related dementias (ADRD). Limited studies have assessed the impacts of ADRD on colorectal cancer screening use and knowledge, and no studies have focused on the associated health disparities. Objectives: To examine the utilization, knowledge, and associated health disparities of colorectal cancer screening in older adults with ADRD. Methods: This study used the Medicare Current Beneficiary Survey from 2015 to 2018. Two types of colorectal cancer screening, including fecal occult blood test (FOBT) and colonoscopy/sigmoidoscopy, were measured. The colorectal cancer screening knowledge was evaluated by asking if the participants have heard of two screening methods and whether they knew Medicare pays for colorectal cancer screenings. Logistic regression models were used to examine the impact of ADRD diagnosis on the utilization and knowledge of colorectal cancer screening. Results: The overall colorectal cancer screening rate in older adults increased from 86.4% to 88.96% from 2015 to 2018. Patients with AD were 39% (OR: 0.61; 95% CI: 0.50–0.76) less likely and those with RD were 25% (OR: 0.75; 95% CI: 0.62–0.91) less likely to use any colorectal cancer screening when compared to older adults without ADRD. The rate of knowledge of colonoscopy/sigmoidoscopy remained high between 84.23% and 84.57% while the knowledge of FOBT increased from 64.32% to 78.69% during the study period. Compared to older adults without ADRD, those with AD were 77% (OR: 1.77; 95% CI: 1.12–2.81) more likely to hear of colonoscopy/sigmoidoscopy. The rate of knowledge of Medicare pay for colorectal cancer screening increased from 42.19% to 45.27% during the study period. Compared to older adults without ADRD, those with AD were 19% (OR: 0.81; 95% CI: 0.70–0.94) less likely to know that Medicare pays for colorectal cancer screening. Conclusion: ADRD was significantly associated with colorectal cancer screening utilization and knowledge. In addition, this study identified health disparities in race/ethnicity, gender, and urban/rural residence in colorectal cancer screening use and knowledge.